Ethnic Studies and Good Teaching: A Research Summary - Jewett, Michelle (Allies for Education, 2018)
This article provides a brief context for Ethnic Studies (ES) and summarizes research findings on the positive affects ES courses have on students. Research-based criteria for effective Ethnic Studies courses are examined and applied to sample curricula from two California school districts.